EFEKTIFITAS METARHIZIUM DAN PUPUK ORGANIK TERHADAP PERKEMBANGAN HAMA URET (Lepidiota stigma) PADA TANAMAN TEBU - HARYUNI HARYUNI (JURNAL ILMIAH AGRINECA, 2014)
The aims of this research are to study the effektivity of Metarhizium anisopliae fungus with organic fertilizer to Lepidiota stigma  pest on Sugarcane plant (Saccharum officinarum L.). The research conducted at. Central of Java Province in Pejagran Village , Glagah, Purworejo,Sidomukti, for eleven (11) months from Mei 2013 to April 2014. The research used Completely Random Design (CRD) Factorial two (2) factors. First factor: Levels of M. anisopliae fungus that consisted of three (3) levels, which is 1) Without M. anisopliae fungus , 2) Inoculation M. anisopliae from fungus 8 kh/ha, 3)  Inoculation M. anisopliae from fungus 16 kh/ha. Second factor levels of organic fertility that consisted of five (5) levels, which is 1) Without organic fertility , 2)  Levels of organic fertilizer 6 ton/ha, 3)  Levels of organic fertilizer  8 ton/ha., 4)  Levels of organic fertilizer 10 ton/ha, 5)  Levels of organic fertilizer 12 ton/ha  Each consisted of three (3) replications. Data observation was analyzed by using Analysis of Variance (ANOVA), if there are differences among treatment continued with Test of Duncan Multiple Range Test (DMRT) at 5 % level. Result of research showed that  M. anisopliae fungus increase to high of plant, so that decrease to Lepidioda stigma instar 1-2, and L stigma instar 3-4.